Is It Possible For Money Laundering To Become An Independent Crime In The Future? - Yohanes Priyana (Yuridika, 2026)
One crucial aspect of efforts to prevent and eradicate money laundering is the relationship between the predicate offense and the crime of money laundering. Conceptually, it is final and undisputed that money laundering is always a derivative crime that follows an offense that generates money or wealth. However, in the context of accelerating law enforcement, money laundering can be treated as a standalone crime if it is based on the absence of the obligation to prove the predicate offense. This allows the prosecution of money laundering separately without the need to prove the predicate crime first, as stipulated in Article 69 of the Law on the Prevention and Eradication of the Crime of Money Laundering (UU PP TPPU). Furthermore, defendants are obliged to prove that their assets are not the result of criminal acts, as stipulated in Article 77 of the UU PP TPPU. Additionally, in the future, efforts to reform the prevention and eradication of money laundering should include strengthening the Financial Transaction Reports and Analysis Center (PPATK) and expanding the authority of the Corruption Eradication Commission (KPK) to investigate and prosecute money laundering cases.